Lung Abnormalities in Liver Cirrhosis - Muli Yaman (Universitas Airlangga, 2023)
Regardless of preexisting lung illness, patients suffering from liver cirrhosis, especially decompensated liver cirrhosis, can develop distinct pulmonary complications. Liver cirrhosis patients should be assessed for hepatopulmonary syndrome (HPS), portopulmonary hypertension (PoPH), hepatic hydrothorax (HH) and spontaneous bacterial empyema (SBEM) which are the most clinically significant pulmonary consequences, in particular when dyspnea develops in conjunction with hepatic cirrhosis. These entities differ in terms of pathophysiology, clinical characteristics, diagnosis and suitable treatment options. This emphasize the need of specific diagnostic algorithm in liver cirrhosis patients presenting with dyspnea or other pulmonary symptoms. These pulmonary complications might be rare in patients with liver cirrhosis and portal hypertension, but these complications might carry significant morbidity and mortality risks and, therefore, strong clinical suspicion is required to make an early accurate diagnosis. There are several medical therapies available for each condition in the multiple studies but most of the treatments and procedures does not have significant benefit or have short lived benefit. The only treatment that changes the clinical prognosis of decompensated cirrhosis effectively in long term is liver transplantation. However, liver transplantation also needs careful considerations as on some cases it might increase the risk of morbidity and mortality.